Prevalence and clinical implications of valvular calcification on coronary computed tomography angiography. (11th December 2020) - Williams, Michelle C; Massera, Daniele; Moss, Alastair J; Bing, Rong; Bularga, Anda; Adamson, Philip D; Hunter, Amanda; Alam, Shirjel; Shah, Anoop S V; Pawade, Tania; Roditi, Giles; van Beek, Edwin J R; et al.
Abstract: Aims: Valvular heart disease can be identified by calcification on coronary computed tomography angiography (CCTA) and has been associated with adverse clinical outcomes. We assessed aortic and mitral valve calcification in patients presenting with stable chest pain and their association with cardiovascular risk factors, coronary artery disease, and cardiovascular outcomes. Methods and results: In 1769 patients (58 ± 9 years, 56% male) undergoing CCTA for stable chest pain, aortic and mitral valve calcification were quantified using Agatston score. Aortic valve calcification was present in 241 (14%) and mitral calcification in 64 (4%). Independent predictors of aortic valve calcification were age, male sex, hypertension, diabetes mellitus, and cerebrovascular disease, whereas the only predictor of mitral valve calcification was age. Patients with aortic and mitral valve calcification had higher coronary artery calcium scores and more obstructive coronary artery disease. The composite endpoint of cardiovascular mortality, non-fatal myocardial infarction, or non-fatal stroke was higher in those with aortic [hazard ratio (HR) 2.87; 95% confidence interval (CI) 1.60–5.17; P < 0.001] or mitral (HR 3.50; 95% CI 1.47–8.07; P = 0.004) valve calcification, but this was not independent of coronary artery calcification or obstructive coronary artery disease. Conclusion: Aortic and mitral valve calcification occurs in one in six patients with stable chest pain undergoing CCTA and is associated with concomitant coronary atherosclerosis. Whilst valvular calcification is associated with a higher risk of cardiovascular events, this was not independent of the burden of coronary artery disease.